O zasobie leksykalnym słownika Jana Ernestiego z 1689 roku - Kaszewski, Marek (Papers in Linguistics, 2020)
The article discusses the lexical resources of the 17th c. dictionary of Polish written by Jan Ernesti and its potential as a research material for advanced studies of the history of spoken Polish